2020
DOI: 10.1055/s-0040-1708038
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Obese and Morbidly Obese Patients in Same-Day Bilateral Total Knee Arthroplasty from 2009 to 2016

Abstract: As obesity in the United States increases, the proportion of obese and morbidly obese patients undergoing same-day bilateral total knee arthroplasty (sd-BTKA) remains unknown. Therefore, this study analyzed: (1) incidence, (2) patient demographics, (3) patient course, and (4) patient outcomes in obese and morbidly obese patients undergoing sd-BTKA in the United States from 2009 to 2016. The National Inpatient Sample was queried for all sd-BTKA patients from 2009 to 2016, yielding 39,901 obese and 20,394 morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In our study, general and systemic complications such as DVT, AKI, and PE were observed. Remily et al reported that orthopedists should review the risks and benefits of SBTKA in detail, since the overall complication rates are high in both O and MO patients and will cause a long hospital stay [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, general and systemic complications such as DVT, AKI, and PE were observed. Remily et al reported that orthopedists should review the risks and benefits of SBTKA in detail, since the overall complication rates are high in both O and MO patients and will cause a long hospital stay [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…since the overall complication rates are high in both O and MO patients and will cause a long hospital stay [18].…”
Section: Plos Onementioning
confidence: 99%